Flash Spark Plasma Sintering (FSPS) of α and β SiC. Issue 5 (28th February 2016) - Grasso, Salvatore; Saunders, Theo; Porwal, Harshit; Milsom, Ben; Tudball, Adam; Reece, Mike
Abstract : A novel processing methodology that allows combined preheating and Flash‐SPS (FSPS) of silicon carbide‐based materials has been developed. Beta‐SiC (+10 wt% B4 C) powders were densified (Ф 20 mm) up to 96% of their theoretical density in 17 s under an applied pressure of 16 MPa (5 kN). The flash event was attributed to the sharp positive temperature dependence of the electrical conductivity (thermal runaway) of SiC, and a sudden increase in electric power absorption (Joule heating) of the samples after a sufficient preheating temperature (>600°C) was reached. The microstructural evolution was analyzed by examining materials densified by FSPS in the range of 82%–96% theoretical densities. FEM modeling results suggest that the FSPS heating rate was of the order of 8800°C/min. A comparative analysis was done between FSPS and reference samples (sintered using conventional SPS in the temperature range of 1800°C–2300°C). This allowed for a better understanding of the temperatures generated during FSPS, and in turn the sintering mechanisms. We also demonstrated the scalability of the FSPS process by consolidating a large α‐SiC disk (Ф 60 mm) in about 60 s inside a hybrid SPS furnace equipped with an induction heater, which allowed us to achieve sufficient preheating (1600°C) of the material to achieve FSPS.